Characteristics and Typology Of Artistic Language "Gunki Monogatari" - Javokhir Abubakirov (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Kamakura period includes the period from 1185 to 1333. The peculiarity of this period is that with the change of power, it had its effect on literature, and the literary theme changed, the focus on heroism and old values, loyalty, bravery and new worldviews changed. This thing served to increase the military power in the society. In general, all events and feelings in human life are the main topic of literature. In 1192, the great leader of the "eastern" (Kanto) samurai detachments - Minamoto Yoritomo, after a long struggle, declares himself sei-taishogun, that is, the "supreme military leader" of Japan, thus the true and hereditary becomes a ruler. becomes the true and hereditary ruler of the whole country. Nevertheless, the Heian kings retain their supreme authority, but in fact begin to play almost exclusively the role of the "high priests" of their people - the supreme ministers of Shintoism. The Heian monarchy was replaced by a "shogunate" - a military system of government. The new management system also had an impact on literature. Now new genres have started to appear in it. First, the circle of readers has completely changed. Literature based on a new life, new state forms and a new culture, literary works characteristic of samurai culture began to be created. The student began to belong to a different social environment with a unique worldview. The boundaries of this circle have also expanded significantly. They began to attract an unprecedented number of readers in Japan. Literature began to be read not only by new people, but also lost its previous, essentially more exotic character and acquired a "wide" readership. A new author, a new reader, a new environment revived the new literature. And the main reason for this was the day